The dynamics of entrepreneurship evidence from the Global Entrepreneurship Monitor data - Minniti, Maria (Oxford : Oxford University Press, 2011)
As governments across the world look to entrepreneurship as a way to increase the wealth and well-being of their countries this volume brings together leading scholars to provide a comprehensive overview of entrepreneurial activity based on empirical data.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Entrepreneurship; Industry